A luminescent composite nanomaterial and its preparation method and application in anti-counterfeiting or temperature sensing
Through Tm3+/Yb3+ co-doped double perovskite material, the stability and complexity of nanomaterials in temperature measurement and anti-counterfeiting are solved, efficient temperature detection and multiple anti-counterfeiting functions are achieved, the preparation process is simplified and the cost is reduced. .
Patent Information
- Application Number
- CN202411488109.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing nanomaterials have unstable performance in temperature measurement, complex signals and difficult to extract, complex preparation processes and high cost, and it is difficult to achieve multiple anti-counterfeiting and identification in terms of anti-counterfeiting.
Using Cs2NaMCl6:xTm3+/zYb3+ light-emitting composite nanomaterial, Tm3+/Yb3+ co-doped bisperovskite material, enhance the fluorescence intensity and realize temperature detection. The preparation method includes CsCl, NaCl, M salt at 20℃-25℃ , YbCl3 and TmCl3 were mixed with hydrochloric acid solution to optimize the doping ion concentration, reaction time and hydrochloric acid solution concentration to obtain efficient luminescence composite nanomaterials.
It realizes multiple anti-counterfeiting and temperature detection with good stability, simplifies the industrial inspection process, reduces the preparation cost, and expands the temperature measurement range.
Smart Images

Figure CN118995220B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of luminescent composite nanomaterials, anti-counterfeiting and temperature measurement, and in particular relates to a luminescent composite nanomaterial and a preparation method thereof and an application thereof in anti-counterfeiting or temperature sensing. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Currently, nanomaterials have been used in many aspects of daily life, but some existing nanomaterials still have many problems in temperature measurement, such as performance changes over time and environmental changes, resulting in poor stability of temperature measurement results, and the temperature-related signal data generated by nanomaterials is sometimes complex, making it difficult to accurately extract temperature information and process it in real time. In addition, some nanomaterials have problems such as complex preparation process, high cost and limited temperature measurement range. In terms of anti-counterfeiting, existing nanomaterials are difficult to meet multiple anti-counterfeiting requirements, such as the single material printing anti-counterfeiting technology is easy to imitate, and complex graphics are difficult to identify.
[0004] Therefore, some studies have used double perovskite materials for the preparation of anti-counterfeiting or temperature sensing fields, but traditional double perovskite materials (Cs2NaBiCl6, Cs2NaTbCl6, Cs2NaErCl6) have low luminescence quantum yields and are difficult to meet the requirements of anti-counterfeiting or temperature sensing. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a luminescent composite nanomaterial, a preparation method thereof and an application in anti-counterfeiting or temperature sensing, which solves the problems of complex preparation process, high cost, difficult signal identification, limited temperature measurement range or easy imitation of anti-counterfeiting technology of traditional luminescent nanomaterials. The luminescent composite nanomaterial of the present invention has good stability and can realize multiple anti-counterfeiting or temperature detection.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides a luminescent composite nanomaterial, wherein the molecular formula of the luminescent composite nanomaterial is Cs2NaMCl6: xTm 3+ / zYb 3+ , wherein M is selected from one of Bi (bismuth), Tb (terbium), and Er (erbium), x is 0.09-0.1, and z is 0.9-1.
[0008] In order to meet the requirements of anti-counterfeiting or temperature sensing, the fluorescence emitted by nanomaterials needs to be vivid, eye-catching and bright for easy identification. The luminescence performance of nanomaterials is strongly dependent on the type of doping elements, the energy transfer between doping elements, and the crystal field of nanoparticles. After long-term research and experimental exploration, the present invention has found that: compared with single doping Tm 3+ (Thulium ion), Yb 3+ Compared with other doping systems, the use of Tm 3+ / Yb 3+ Co-doped double perovskite materials (Cs2NaBiCl6, Cs2NaTbCl6, Cs2NaErCl6) can significantly enhance their fluorescence intensity and emit bright blue, purple or red fluorescence. At the same time, the luminescence intensity can also be linearly fitted with the temperature to achieve temperature detection.
[0009] The second aspect of the present invention provides a method for preparing the above-mentioned luminescent composite nanomaterial, comprising:
[0010] CsCl (cesium chloride), NaCl (sodium chloride), M salt, YbCl3 (ytterbium chloride), TmCl3 (thulium chloride) are mixed evenly with hydrochloric acid solution and water, and reacted at 20°C-25°C. After the reaction is completed, the mixture is dried to obtain a luminescent composite nanomaterial;
[0011] Wherein, the M salt is selected from one of BiCl3 (bismuth chloride), TbCl3 (terbium chloride), and ErCl3 (erbium chloride).
[0012] The concentration of doped ions will affect the luminescence intensity of the nanomaterial. Therefore, the present invention studies the doping amount of YbCl3. Preferably, when the molar ratio of NaCl to YbCl3 is 1:(0.9-1), a better luminescence intensity can be obtained.
[0013] Tm 3+ With Yb 3+ The ratio will affect the transmission of the two ion channels, and thus affect the luminescence intensity of the nanomaterial. Therefore, the present invention studies the doping amount of TmCl3. Preferably, when the molar ratio of YbCl3 to TmCl3 is (0.9-1):0.1, a better luminescence intensity can be obtained.
[0014] The reaction time will affect the yield and purity of the luminescent composite nanomaterial. If the reaction time is too short, the reaction is incomplete, and if the reaction time is too long, the energy consumption is high. Therefore, the present invention studies the reaction time, and preferably, the reaction time is 0.5-2h.
[0015] The concentration of the hydrochloric acid solution will affect the efficiency of the reaction. Therefore, the present invention studies the concentration of the hydrochloric acid solution. Preferably, the mass concentration of the hydrochloric acid solution is 36%-38%.
[0016] The amount of water used will affect the dispersion effect of the raw materials. Therefore, the present invention studies the amount of water used. Preferably, the volume ratio of the hydrochloric acid solution to water is (6-8): (20-25).
[0017] Domestic water inevitably contains metal impurities, which will affect the purity of the composite material during the synthesis process, and further affect its luminescent properties. For this reason, the present invention studies the types of water. Preferably, the water is pure water.
[0018] The third aspect of the present invention provides the use of the above-mentioned luminescent composite nanomaterial in anti-counterfeiting or temperature sensing.
[0019] Beneficial effects of the present invention
[0020] (1) The luminescent composite nanomaterial Cs2NaBiCl6:Tm 3+ / Yb 3+ Emitting blue light at 980nm excitation wavelength, Cs2NaTbCl6:Tm 3+ / Yb 3+ Emitting purple light at 254nm excitation wavelength, Cs2NaErCl6:Tm 3+ / Yb 3+ It emits red light at an excitation wavelength of 980nm, and can achieve different colors of fluorescence emission under the excitation of different wavelengths of excitation light (980nm, 254nm), thereby achieving multiple anti-counterfeiting functions. 3+ / Yb 3+ Under 980nm laser excitation, the material is heated (33℃-300℃), and the fluorescence intensity of the material decreases as the temperature rises, thereby realizing the temperature measurement function.
[0021] (2) The luminescent composite nanomaterial provided by the present invention has a small particle size and a simple detection method, which can effectively reduce the industrial detection process;
[0022] (3) The preparation process of the luminescent composite nanomaterial provided by the present invention is simple and low-cost, which is conducive to industrial large-scale production.
[0023] (4) The luminescent composite nanomaterial prepared by the present invention can be used not only in temperature sensing, but also in the field of anti-counterfeiting, and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0025] Figure 1 It is Cs2NaBiCl6:Tm prepared in Example 1 of the present invention 3+ / Yb 3+ SEM images of nanoparticles;
[0026] Figure 2 It is Cs2NaBiCl6:Tm prepared in Example 1 of the present invention 3+ / Yb 3+ Emission spectra of nanoparticles;
[0027] Figure 3 It is Cs2NaBiCl6:Tm prepared in Example 1 of the present invention 3+ / Yb 3+ X-ray diffraction pattern of nanoparticles;
[0028] Figure 4 It is Cs2NaTbCl6:Tm prepared in Example 2 of the present invention 3+ / Yb 3+ Emission spectrum of nanoparticles excited at 254 nm;
[0029] Figure 5 It is Cs2NaErCl6:Tm prepared in Example 3 of the present invention 3+ / Yb 3+ Emission spectrum of nanoparticles excited at 980 nm;
[0030] Figure 6 It is Cs2NaBiCl6:Tm prepared in Example 1 of the present invention 3+ / Yb 3+ Emission spectra of nanoparticles at different temperatures;
[0031] Figure 7 It is Cs2NaBiCl6:Tm prepared in Example 1 of the present invention 3+ / Yb 3+ Linear fitting diagram of nanoparticle luminescence intensity and temperature;
[0032] Figure 8 It is an anti-counterfeiting image of Cs2NaTbCl6 and Cs2NaErCl6 nanoparticles prepared in Examples 2 and 3 of the present invention excited at 254nm and 980nm;
[0033] Fig. 9This is the color coordinate diagram of the mixed powder of Cs2NaBiCl6, Cs2NaTbCl6, and Cs2NaErCl6 prepared in Examples 1, 2, and 3 of the present invention when excited at 980nm. DETAILED DESCRIPTION
[0034] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0035] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0036] The present invention has no particular limitation on the sources of the reagents in the examples, and commercially available products known to those skilled in the art may be used.
[0037] Example 1
[0038] This example provides Cs2NaBiCl6:Tm 3+ / Yb 3+ The preparation comprises the following steps:
[0039] (1) Weigh cesium chloride (2 mmol), sodium chloride (1 mmol), and bismuth chloride (1 mmol) into a beaker, add YbCl3 (1 mmol), TmCl3 (0.1 mmol), add 6 mL of concentrated hydrochloric acid (mass concentration is 36%), and 20 mL of water, stir evenly, and react for 2 h until the solution is clear.
[0040] (2) Place the clear solution in a drying oven at 60°C for 24 hours to obtain a yellow solid, which is then ground into powder.
[0041] Determine the obtained Cs2NaBiCl6:Tm 3+ / Yb 3+ SEM images of nanoparticles, such as Figure 1 As shown. Figure 1 It can be seen that Cs2NaBiCl6:Tm 3+ / Yb 3+ It is a double perovskite, and its nanoparticles are in the form of flakes.
[0042] Take part of the powder to determine Cs2NaBiCl6:Tm 3+ / Yb 3+ The emission spectrum of Figure 2 As shown, the emission peak is at 456nm, the excitation light source used is 980nm, and the power is 1.2W.
[0043] Cs2NaBiCl6:Tm 3+ / Yb 3+ The X-ray diffraction pattern of the nanoparticles is consistent with the standard card (PDF#77-1831), such as Figure 3 As shown, it is shown that the prepared product is Cs2NaBiCl6:Tm 3+ / Yb 3+ Nanoparticles, pure phase and without any impurities.
[0044] Example 2
[0045] This example provides Cs2NaTbCl6:Tm 3+ / Yb 3+ The preparation comprises the following steps:
[0046] (1) Weigh cesium chloride (2 mmol), sodium chloride (1 mmol), and terbium chloride (1 mmol) into a beaker, add YbCl3 (1 mmol), TmCl3 (0.1 mmol), add 8 mL of concentrated hydrochloric acid (mass concentration is 38%), and 25 mL of water, stir evenly, and react for 0.5 h until the solution is clear.
[0047] (2) Place the clear solution in a drying oven at 60°C for 24 hours to obtain a yellow solid, which is then ground into powder.
[0048] Take part of the powder to determine Cs2NaTbCl6:Tm 3+ / Yb 3+ The emission spectrum of Figure 4 As shown, the emission peak is at 394 nm and the excitation light source used is 254 nm.
[0049] Example 3
[0050] This example provides Cs2NaErCl6:Tm 3+ / Yb 3+ The preparation comprises the following steps:
[0051] (1) Weigh cesium chloride (2 mmol), sodium chloride (1 mmol), and erbium chloride (1 mmol) into a beaker, add YbCl3 (0.9 mmol), TmCl3 (0.1 mmol), 6 mL of concentrated hydrochloric acid (mass concentration is 36%), and 20 mL of water and stir until the solution is clear.
[0052] (2) Place the clear solution in a drying oven at 60°C for 24 hours to obtain a yellow solid, which is then ground into powder.
[0053] Take part of the powder to determine Cs2NaErCl6:Tm 3+ / Yb 3+The emission spectrum of Figure 5 As shown, the emission peak is at 659 nm and the excitation light source used is 980 nm.
[0054] Comparative Example 1
[0055] This comparative example provides the preparation of a mixed powder that produces white light, comprising the following steps:
[0056] (1) Weigh 0.1 g Cs2NaBiCl6, 0.5 g Cs2NaTbCl6, and 0.02 g Cs2NaErCl6, mix well, and add 2 mL ethanol.
[0057] (2) Ultrasonicate for 5-10 minutes to mix the powder evenly, then put it into a drying oven to dry.
[0058] Application Example 1
[0059] The material in Example 1 was used in a temperature sensing experiment, and the specific steps were as follows:
[0060] (1) Take Cs2NaBiCl6:Tm 3+ / Yb 3+ The powder of nanomaterial is placed in a temperature measuring device;
[0061] (2) Using a variable temperature device for heating, and using a spectrometer to test Cs2NaBiCl6:Tm under 980nm laser irradiation 3 + / Yb 3+ The fluorescence spectrum of the composite nanomaterial is obtained to obtain the curve of the fluorescence spectrum changing with temperature, and then this curve can be used to calculate the temperature of the environment in which the composite material is located, such as Figure 6 , Figure 7 As shown, the excitation light source used is 980nm and the power is 1.5W, indicating that Cs2NaBiCl6:Tm 3+ / Yb 3+ The fluorescence emission intensity of the composite nanomaterials decreases with increasing temperature.
[0062] It can be seen that Cs2NaBiCl6:Tm 3+ / Yb 3+ The temperature is detected by the difference in fluorescence intensity of nanomaterials at different temperatures.
[0063] Application Example 2
[0064] The materials in Examples 2 and 3 were used in anti-counterfeiting experiments, and the specific steps were as follows:
[0065] (1) Add 0.4 g Cs2NaTbCl6:Tm to 0.6 mL of ink. 3+ / Yb 3+The nanomaterials were stirred evenly to obtain Cs2NaTbCl6:Tm 3+ / Yb 3+ Nanomaterial ink: 0.2 g Cs2NaErCl6:Tm 3+ / Yb 3 + The nanomaterials were stirred evenly to obtain Cs2NaErCl6:Tm 3+ / Yb 3+ Nanomaterial inks.
[0066] (2) Prepare appropriate cardboard, cover the hollow pattern of "logo", and select "l" area to coat with Cs2NaErCl6:Tm 3+ / Yb 3+ The remaining part (i.e., the “ogo” area) is coated with an ink containing Cs2NaTbCl6:Tm 3+ / Yb 3+ The ink of nanoparticles uses the distribution pattern as the encryption key and is dried to obtain the result. During verification, different wavelengths (254nm, 980nm) are used for excitation, the distribution pattern is read and compared with the preset key. Figure 8 As shown, Cs2NaTbCl6:Tm prepared in Examples 2 and 3 3+ / Yb 3+ 、Cs2NaErCl6:Tm 3+ / Yb 3+ The anti-counterfeiting pattern of the luminescent composite nanomaterial uses an excitation light source of 254nm and 980nm.
[0067] It can be seen that based on Cs2NaErCl6:Tm 3+ / Yb 3+ Nanoparticles, Cs2NaTbCl6:Tm 3+ / Yb 3+ The luminescent pattern of nanoparticles under the excitation wavelength is used to achieve multiple anti-counterfeiting of the pattern.
[0068] Application Example 3
[0069] The materials in Comparative Example 1 were used in an LED (light emitting diode) lighting experiment, and the specific steps were as follows:
[0070] Weigh Cs2NaBiCl6, Cs2NaTbCl6, and Cs2NaErCl6 and mix them evenly. Add 2 mL of ethanol and perform ultrasonication to mix the powders evenly. Put the powders into a drying oven and dry them.
[0071] like Fig. 9 As shown, the excitation light source used is 980nm and the power is 1.2W.
[0072] It can be seen that compared with Comparative Example 1, Examples 1-3 have obvious changes in fluorescence properties and can meet the application requirements of temperature measurement or anti-counterfeiting.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A luminescent composite nanomaterial, characterized in that: The molecular formula of the luminescent composite nanomaterial is Cs2NaMCl6:xTm 3+ / zYb 3+ , wherein M is selected from one of Bi, Tb, and Er, x is 0.09-0.1, and z is 0.9-1.
2. A method for preparing the luminescent composite nanomaterial according to claim 1, characterized in that: include: CsCl, NaCl, M salt, YbCl3, TmCl3, hydrochloric acid solution and water are uniformly mixed, reacted at 20°C-25°C, and dried after the reaction is completed to obtain a luminescent composite nanomaterial; Wherein, the M salt is selected from one of BiCl3, TbCl3, and ErCl3.
3. The method for preparing the luminescent composite nanomaterial according to claim 2, characterized in that: The molar ratio of NaCl to YbCl3 is 1:(0.9-1).
4. The method for preparing the luminescent composite nanomaterial according to claim 2, characterized in that: The molar ratio of YbCl3 and TmCl3 is (0.9-1):0.
1.
5. The method for preparing the luminescent composite nanomaterial according to claim 2, characterized in that: The reaction time is 0.5h-2h.
6. The method for preparing the luminescent composite nanomaterial according to claim 2, characterized in that: The mass concentration of the hydrochloric acid solution is 36%-38%.
7. The method for preparing the luminescent composite nanomaterial according to claim 2, characterized in that: The volume ratio of the hydrochloric acid solution to water is (6-8): (20-25).
8. The method for preparing the luminescent composite nanomaterial according to claim 2, characterized in that: The water is purified water.
9. Use of the luminescent composite nanomaterial according to claim 1 in anti-counterfeiting or temperature sensing.
